Ecological Traits Influencing Anthropogenic Debris Ingestion by Herbivorous Reef Fishes - Cardozo-Ferreira, Gabriel C.; Calazans, Thayane L.; Benevides, Larissa J.; Luiz, Osmar J.; Ferreira, Carlos E. L.; Joyeux, Jean-Christophe (Frontiers in Marine Science, 2021)
One of the most conspicuous marks of the Anthropocene worldwide is the ubiquitous pollution by long lifespan materials (e.g., plastic). In marine habitats, anthropogenic debris are observed from floating on the surface to deposited on the substrate or ingested by wildlife at different food web levels. However, the link between feeding strategy types and debris ingestion by reef fishes remains poorly explored. We analyzed the gut contents of three nominally herbivorous fishes along the Brazilian coast: the doctorfish Acanthurus chirurgus, the parrotfish, Sparisoma axillare, and the chub Kyphosus vaigiensis. Individual [i.e., total length (TL)] and species-level functional traits, as well sites with distinct environmental features (i.e., tourism activity intensity, fishing pressure, and distance from the coast), were tested as predictors of the concentration of debris found inside individual fish guts. Debris found were quantified, measured, and classified accordingly to color and shape. We found debris in 52.7% of individuals. Debris ranged from 0.10 to 11.75 mm, and the frequency of occurrence and ingestion rate (number of debris per individual) varied among species, being higher for the scraper species S. axillare (95.7% and 4.9 ± 1.2, respectively) and A. chirurgus (74.6% and 1.64 ± 0.34), than for the browser K. vaigiensis (55.8% and 0.83 ± 0.24). TL, scraping feeding mode, and the most impacted location were positively related to debris ingestion rate. Our work revealed a higher vulnerability of an ecologically important trophic group to debris ingestion and of an already threatened species according to Brazilian red list. Besides the increasing number of species contaminated by anthropogenic debris, its effect on fish biology and physiology remains poorly understood. Understanding these links would improve conservation planning as species contamination could act as a proxy for environmental pollution on marine habitats.